A heat-resistant and shock-resistant PPO alloy and preparation process
Through the preparation and application of modified nanoboronitride fillers, the problem of insufficient thermal conductivity and mechanical properties of PPO alloys is solved, and the thermal impact resistance and impact resistance of PPO alloys is improved, which is suitable for the automotive industry and electronic and electrical fields.
Patent Information
- Application Number
- CN202410841716.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-26
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-06-26
AI Technical Summary
The existing PPO alloys have shortcomings in improving thermal conductivity and mechanical properties, and are difficult to be widely used in the automotive industry and electronic and electrical fields. At the same time, the dispersion of nanofillers affects material performance.
Modified nanoboronitride filler is used to form modified filler through ultrasonic dispersion, acidification treatment and surface modification, which improves its dispersion performance and interface compatibility in PPO alloys, thereby forming a thermal network structure and enhancing mechanical properties.
It significantly improves the thermal conductivity, mechanical properties and impact resistance of PPO alloys, improves the interfacial compatibility of nanofillers in the material, and extends the durability of use in high temperature environments.
Smart Images

Figure BDA0004915156270000141 
Figure BDA0004915156270000151
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer resin materials, and in particular to a heat-resistant and impact-resistant PPO alloy and a preparation process. Background Art
[0002] Polyphenylene Oxide (PPO) is a high-performance polymer material with good thermal stability, mechanical properties and chemical corrosion resistance. However, pure PPO has poor processing performance and high brittleness, which limits the wide application of pure PPO. Therefore, PPO is usually blended or alloyed with other polymers to modify PPO to improve processing performance and mechanical properties.
[0003] At present, the commonly used modification methods of PPO alloys mainly include graft copolymerization, which introduces functional monomers into the PPO molecular chain through chemical reactions to make it more compatible with other polymers. For example, maleic anhydride is grafted onto PPO to improve the compatibility of PPO and PA. There is also a blending modification method, which uses auxiliary materials such as compatibilizers to improve the compatibility and interfacial bonding properties of various different polymers. There is also nano-composite technology, which introduces nano-scale fillers into the PPO matrix to improve the mechanical properties, thermal stability and barrier properties of PPO alloys.
[0004] However, although the blending modification method and grafting copolymerization method can improve the compatibility of PPO with other polymers to a certain extent, these modification methods do not significantly improve the thermal conductivity and mechanical properties of PPO alloys, making it difficult to apply them on a large scale in the automotive industry and the electrical and electronic fields. The use of nanofiller modification methods can improve the thermal conductivity and mechanical properties of PPO alloys, but the dispersion of nanofillers in the PPO matrix will directly affect the material properties. Therefore, it is urgent to provide a solution to improve the above problems. Summary of the invention
[0005] The purpose of the present invention is to provide a heat-resistant and shock-resistant PPO alloy and a preparation process.
[0006] The invention provides a heat-resistant and impact-resistant PPO alloy, which comprises the following components in parts by weight: 50-60 parts of PPO resin, 20-30 parts of PP resin, 10-15 parts of silicone resin, 5-10 parts of modified filler, and 5-25 parts of functional additives; the preparation method of the modified filler comprises: ultrasonically dispersing nano boron nitride in ethanol to obtain a dispersion; acidifying the pH value of the dispersion to 2-3, ultrasonically treating for 1-2 hours, separating, washing, and drying to obtain an activated filler; ultrasonically dispersing the activated filler into a melamine solution, and then separating to obtain a modified intermediate; ultrasonically dispersing the modified intermediate in a dopamine hydrochloride solution, reacting for 10-15 hours at pH=8-9, and then separating and drying to obtain the modified filler.
[0007] The PPO alloy provided by the present invention uses PPO resin as a matrix material to provide basic heat resistance and mechanical properties. At the same time, the addition of PP resin and silicone resin can effectively improve the toughness, processing performance, heat resistance and oxidation resistance of the overall material, and the functional additives can further improve the overall processability and use performance of the material. By modifying the nano-boron nitride, the dispersion performance of the modified filler in the alloy material can be effectively improved, thereby forming a framework network, which can improve the thermal conductivity of the PPO alloy material as a whole, enhance the mechanical properties, and improve the interface compatibility of the modified filler in the material.
[0008] Optionally, when the modified intermediate is ultrasonically dispersed in the dopamine hydrochloride solution, the mass mixing ratio of the modified intermediate to the dopamine hydrochloride solute in the dopamine hydrochloride solution is (5-10):1.
[0009] Optionally, when the nano-boron nitride is ultrasonically dispersed in ethanol to obtain a dispersion liquid, the method includes: mixing the nano-boron nitride and a coupling agent, adding the mixture into ethanol, and ultrasonically dispersing the mixture to obtain a dispersion liquid.
[0010] Optionally, the coupling agent includes at least one of a silane coupling agent and a titanate coupling agent.
[0011] Optionally, the mass mixing ratio of the nano boron nitride to the coupling agent is 1:(0.2-0.3).
[0012] Optionally, the average particle size of the nano boron nitride is 20-100 nm.
[0013] Optionally, the functional additives include a compatibilizer, a toughening agent, a flame retardant, an antioxidant, a lubricant, and a dispersant.
[0014] Optionally, the toughening agent includes at least one of chlorinated polyethylene, ethylene-vinyl acetate copolymer, and nitrile resin.
[0015] Optionally, the flame retardant includes at least one of polyphosphoamine, p-hydroxybenzoic acid, and triisobutylphenyl phosphate.
[0016] Optionally, the antioxidant includes at least one of dialkyl pentaerythritol diphosphite, dioctadecyl pentaerythritol diphosphite, bis(2,4-di-tert-butylphenol)pentaerythritol diphosphite, and tetrakis(2,4-di-tert-butylphenyl-4,4'-biphenyl)bisphosphate.
[0017] Optionally, the dispersant includes at least one of polyvinyl alcohol, casein and cellulose.
[0018] Optionally, the following components are included in parts by weight: 53-57 parts of PPO resin, 25-27 parts of PET resin, 12-15 parts of silicone resin, 7-8 parts of modified filler, 2-3 parts of compatibilizer, 3-5 parts of toughening agent, 5-10 parts of flame retardant, 1-2 parts of antioxidant, 1-2 parts of lubricant, and 1-2 parts of dispersant.
[0019] Optionally, the organic silicone resin includes a titanium-containing organic silicone resin and a boron-containing organic silicone resin, and the mass mixing ratio of the titanium-containing organic silicone resin to the silicon-containing organic silicone resin is (6-8):(4-7).
[0020] In a second aspect, the present invention also provides a preparation process of a PPO alloy, comprising the following steps: pre-mixing a PPO resin, a PP resin, a silicone resin and a functional additive to obtain a primary mixture; mixing the primary mixture with a modified filler, melt-blending the mixture at 200-240°C, and extruding and pelletizing the mixture to obtain alloy particles; and injection molding the alloy particles at 200-250°C to obtain a heat-resistant and impact-resistant PPO alloy. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meanings understood by people with general skills in the field to which the present invention belongs.
[0022] The invention provides a heat-resistant and impact-resistant PPO alloy, which comprises the following components in parts by weight: 50-60 parts of PPO resin, 20-30 parts of PP resin, 10-15 parts of organic silicon resin, 5-10 parts of modified filler and 5-25 parts of functional additive.
[0023] In fact, adding PPO resin as a matrix material has excellent heat resistance, dimensional stability and electrical insulation properties. At the same time, PPO resin can provide basic mechanical properties and heat resistance in the alloy material. In addition, the higher glass transition temperature of PPO resin enables the material as a whole to maintain good mechanical strength and morphological stability at high temperatures.
[0024] Specifically, PPO resin can be purchased from Nantong Xingchen Synthetic Materials Co., Ltd. with the brands LXR035 (intrinsic viscosity 35.00-38.00, volatile content <0.45%, melt index 20.00-35.00 / (300°C, 10kg)), LXR040 (intrinsic viscosity 38.00-43.00, volatile content <0.45%, melt index 6.00-20.00 / (300°C, 10kg)), LXR045 (intrinsic viscosity 43.00-48.00, volatile content <0.45%, melt index 8.00-15.00 / (315°C, 10kg)), and LXR050 (intrinsic viscosity 48.00-53.00, volatile content <0.45%, melt index 4.00-8.00 / (315°C, 10kg)).
[0025] In fact, PP resin has good toughness, chemical corrosion resistance and processing performance. By blending PP resin with PPO resin, the toughness and processing performance of PPO alloy material can be improved while maintaining heat resistance. The addition of PP resin helps to reduce the overall density of the material and comprehensively improve the processing performance and impact resistance.
[0026] Specifically, PP resin can be purchased from SK Chemical (Suzhou) Co., Ltd. with the brand name ES-110M (acid value 5.5 KOHmg / g, hydroxyl value 8 KOHmg / g, glass transition temperature 65°C, weight average molecular weight 13.5×10 3 ), or high gloss PP resin (softening point 1005-115°C, acid value ≤7KOHmg / g, viscosity 100-200), high adhesion PP resin (viscosity 310), and Hyosung PP tackifying resin (softening point 100-120°C, acid value ≤1KOHmg / g) purchased from Shenzhen Yoshida Chemical Co., Ltd.
[0027] In fact, silicone resin has excellent heat resistance, weather resistance and electrical insulation properties, and can maintain structural stability at high temperatures. After adding it to PPO alloy, it can effectively improve the heat resistance and oxidation resistance of PPO alloy, and at the same time, it can also improve the surface smoothness and wear resistance of PPO resin after injection molding, and further increase the service life of PPO alloy in high temperature environment. In fact, adding functional additives to PPO alloy resin can improve the comprehensive performance of the material, making PPO alloy have the effect of conventional additives.
[0028] In some embodiments, the organosilicon resin includes a titanium-containing organosilicon resin and a boron-containing organosilicon resin, and the mass mixing ratio of the titanium-containing organosilicon resin to the silicon-containing organosilicon resin is (6-8):(4-7).
[0029] In fact, adding titanium-containing silicone resin to PPO alloy can effectively increase the thermal decomposition temperature of PPO alloy, prevent PPO alloy from decomposing and deforming at high temperature, and improve the overall heat resistance and mechanical properties. In addition, titanium-containing silicone resin can achieve good synergistic effect with boron-containing silicone resin, thereby comprehensively improving the heat resistance and mechanical strength of PPO alloy.
[0030] Specifically, the preparation method of the titanium-containing silicone resin includes: mixing and dissolving 10 parts of trimethylchlorosilane, 20 parts of tetraethoxysilane and 2 parts of n-butyl titanate in an aqueous solution with a volume fraction of 30% ethanol, stirring and reacting at 80°C for 3 hours and then cooling to room temperature, extracting with toluene and separating the organic phase, and then spin-drying and recovering the toluene to obtain the titanium-containing silicone resin.
[0031] Specifically, the preparation method of the boron-containing silicone resin includes: dissolving 3 mol of phenyltriethoxysilane, 3 mol of dimethyldiethoxysilane and 2 mol of boric acid in anhydrous ethanol to obtain a dissolving solution; adjusting the pH value of the dissolving solution to 1-2 with hydrochloric acid, stirring and hydrolyzing the solution for 2 hours to obtain a hydrolyzed solution; stirring and reacting the hydrolyzed solution at 100°C for 2 hours, and then distilling under reduced pressure to obtain the boron-containing silicone resin.
[0032] Specifically, the preparation method of the modified filler comprises the following steps:
[0033] S1, ultrasonically dispersing nano-boron nitride in ethanol to prepare a dispersion;
[0034] S2, acidifying the pH of the dispersion to 2-3, then ultrasonicating for 1-2 hours, separating, washing and drying to obtain an activated filler;
[0035] S3, ultrasonically dispersing the activated filler into the melamine solution and then separating to obtain a modified intermediate;
[0036] S4. Ultrasonic dispersion of the modified intermediate in a dopamine hydrochloride solution, reacting at pH = 8-9 for 10-15 hours, and then separating and drying to obtain a modified filler.
[0037] In step S1, since nano-boron nitride is prone to agglomeration, the nano-boron nitride is ultrasonically dispersed in ethanol, which can effectively break up the agglomerated nano-boron nitride through the ultrasonic effect, so that the nano-boron nitride is evenly dispersed in the ethanol to form a uniform dispersion.
[0038] In step S2, the nano-boron nitride is ultrasonically dispersed in an acid solution, which can make the surface of the nano-boron nitride carry a positive charge and improve the surface activity of the boron nitride. At the same time, the ultrasonic treatment can further improve the dispersibility of the boron nitride in the dispersion, thereby improving the surface activation effect, and after drying treatment, the reactivity of the activated filler can be improved.
[0039] In step S3, the surface of the activated filler is preliminarily modified by melamine groups, melamine reacts with the active sites on the surface of nano-boron nitride to form stable chemical bonds, and melamine is evenly modified on the surface of boron nitride by ultrasonic treatment, and the obtained modified intermediate has better interface bonding ability.
[0040] In step S4, the modified intermediate is further surface-modified by introducing dopamine groups, which can self-polymerize on the surface of the modified intermediate to form a uniform polydopamine coating layer. The melamine on the surface of the modified intermediate can effectively improve the bonding strength with the polydopamine coating layer. At the same time, the polydopamine coating layer can further stabilize the nano-boron nitride structure and introduce more active sites, further improving the interface bonding ability between the modified filler and the PPO alloy resin matrix.
[0041] In fact, adding modified fillers into PPO alloys and blending the modified fillers with the resin matrix to form a thermally conductive network structure can not only improve the overall thermal conductivity of the PPO alloy, but also facilitate the rapid conduction of heat, thereby improving the heat resistance of the PPO alloy itself, and can effectively prevent local overheating and heat accumulation, and effectively extend the durability and heat aging resistance in high temperature environments.
[0042] In addition, after surface modification of nano-boron nitride, the interface bonding performance between nano-boron nitride and the resin matrix can be improved, the interface bonding force can be enhanced, and stress transfer and dispersion can be facilitated, thereby improving the overall mechanical properties and impact resistance of the PPO alloy material; in addition, nano-boron nitride itself has high strength and high modulus characteristics. After forming a network structure in the PPO alloy, it can play a role in strengthening and toughening, thereby comprehensively improving the impact resistance and overall mechanical properties of the PPO alloy.
[0043] Furthermore, after introducing melamine groups and polydopamine groups on the surface of nano-boron nitride, they can form good interfacial interactions with polar groups in the resin matrix, thereby improving interfacial compatibility and bonding strength. At the same time, they can also improve the dispersibility of nano-boron nitride in the resin matrix and effectively prevent the self-agglomeration of nano-boron nitride.
[0044] In some embodiments, the average particle size of the nano boron nitride used in step S1 is 10-30 nm. By using boron nitride with a small particle size, the specific surface area of boron nitride can be effectively increased, thereby increasing the surface active sites of boron nitride, which is beneficial for surface modification, and at the same time can improve the dispersion and uniformity of the modified filler in the resin matrix.
[0045] In fact, the nano-boron nitride used in step S1 can be a conventional commercially available product, such as nano-boron nitride powder purchased from Shanghai Xiaohuang Nanotechnology Co., Ltd. with item numbers XH-BN-80 (average particle size 80nm, purity >99.9%, hexagonal crystal form) and XH-BN-100 (average particle size 100nm, purity >99.9%, hexagonal / cubic crystal form).
[0046] In some embodiments, when performing step S1 to disperse the nano-boron nitride in ethanol, the solid-liquid ratio of the nano-boron nitride in ethanol is 0.05-0.08 g / mL, so that the nano-boron nitride can be evenly dispersed in the ethanol and the ethanol can fully infiltrate the nano-boron nitride.
[0047] In fact, when performing step S1, the nano boron nitride is dispersed in ethanol, transferred to a closed container, and heated in an ultrasonic state until the ethanol boils, and then cooled to room temperature after boiling under pressure for 1-2 hours to obtain a dispersion. By boiling the ethanol, the nano boron nitride can be further evenly dispersed, and the ethanol can clean the surface of the nano boron nitride and deeply infiltrate it.
[0048] In some embodiments, when executing step S1, the steps include: mixing the nano-boron nitride and the coupling agent and then putting them into ethanol, and preparing the dispersant after ultrasonic dispersion. In fact, when the nano-boron nitride and the coupling agent are mixed and put into ethanol, it is helpful to improve the dispersibility of the nano-boron nitride in ethanol, and the coupling agent can perform preliminary surface activation on the nano-boron nitride.
[0049] Specifically, when the nano boron nitride is mixed with the coupling agent, the mass mixing ratio of the nano boron nitride to the coupling agent is 1:(0.2-0.3). In fact, the coupling agent includes at least one of a silane coupling agent and a titanate coupling agent.
[0050] More specifically, the silane coupling agent includes at least one of methyltrimethoxysilane, vinyltrimethoxysilane, phenyltrimethoxysilane, diethylaminomethyltriethoxysilane, anilinemethyltriethoxysilane, and dichlorodimethylsilane, and may also include at least one of KH-540, KH-550, and KH-792.
[0051] More specifically, the titanate coupling agent includes at least one of isopropyl triisostearate titanate, isopropyl trioleate titanate, diisopropyl di(acetylacetonate) titanate, bis(dioctyl pyrophosphate) ethylene titanate, and isopropyl tri(dioctyl pyrophosphate) titanate.
[0052] In some embodiments, when performing the acidification step S2, concentrated sulfuric acid is added dropwise to the dispersion and quickly stirred and mixed. In fact, the acidity in the dispersion can be effectively controlled by adding concentrated sulfuric acid dropwise, which is beneficial for activating the surface of the nano-boron nitride.
[0053] In some embodiments, when performing step S2 of separation, washing and drying, the mixed dispersion after acidification and ultrasonic treatment is filtered, and the solid obtained by filtration is washed alternately with deionized water and ethanol, and then transferred to a 50° C. drying oven and dried to constant weight.
[0054] In some embodiments, when performing step S3 to ultrasonically disperse the activated filler into the melamine solution, the melamine solution is specifically a melamine acetic acid solution, and the mass mixing ratio of the activated filler to the melamine solute in the melamine solution is 1:(10-20). In fact, by adjusting the mass mixing ratio of the activated filler to melamine, the surface modification morphology and modification amount of the activated filler by melamine can be adjusted.
[0055] In some embodiments, when the modified intermediate is ultrasonically dispersed in the dopamine hydrochloride solution in step S4, the mass mixing ratio of the modified intermediate to the dopamine hydrochloride solute in the dopamine hydrochloride solution is (5-10): 1. In fact, by regulating the mass mixing ratio of the modified intermediate to dopamine hydrochloride, the polymerization amount of dopamine hydrochloride on the surface of the modified intermediate can be regulated. Specifically, the dopamine hydrochloride solution used is a dopamine hydrochloride aqueous solution.
[0056] Specifically, the functional additives used in the PPO alloy include compatibilizers, toughening agents, flame retardants, antioxidants, lubricants, and dispersants. By adding a variety of additive materials to the PPO alloy, the comprehensive performance of the PPO alloy can be effectively improved. In fact, the additive materials that can be added to the PPO alloy can be additive materials commonly used in the art, so that the PPO alloy has corresponding characteristics.
[0057] In some embodiments, the compatibilizer includes at least one of PP-G-MAH, PE-G-MAH, POE-G-MAH, EPDM-G-MAH, and SEBS-G-MAH.
[0058] In some embodiments, the toughening agent includes at least one of chlorinated polyethylene, ethylene-vinyl acetate copolymer, and nitrile resin.
[0059] In some embodiments, the flame retardant includes at least one of polyphosphoamine, p-hydroxybenzoic acid, and triisobutylphenyl phosphate.
[0060] In some embodiments, the antioxidant includes at least one of dialkyl pentaerythritol diphosphite, dioctadecyl pentaerythritol diphosphite, bis(2,4-di-tert-butylphenol)pentaerythritol diphosphite, and tetrakis(2,4-di-tert-butylphenyl-4,4'-biphenyl)bisphosphate.
[0061] In some embodiments, the lubricant includes at least one of erucamide, oleamide, stearamide, zinc stearate, magnesium stearate, and calcium stearate.
[0062] In some embodiments, the dispersant includes at least one of polyvinyl alcohol, casein, and cellulose.
[0063] In some embodiments, the PPO alloy includes the following components in parts by weight: 53-57 parts of PPO resin, 25-27 parts of PET resin, 12-15 parts of silicone resin, 7-8 parts of modified filler, 2-3 parts of compatibilizer, 3-5 parts of toughening agent, 5-10 parts of flame retardant, 1-2 parts of antioxidant, 1-2 parts of lubricant, and 1-2 parts of dispersant.
[0064] The present invention also provides a preparation process of a heat-resistant and impact-resistant PPO alloy, comprising the following steps: premixing PPO resin, PP resin, silicone resin and functional additives to obtain a primary mixture; mixing the primary mixture with a modified filler, melt-blending the mixture at 200-240° C., and extruding and pelletizing the mixture to obtain alloy particles; and injection molding the alloy particles at 200-250° C. to obtain a heat-resistant and impact-resistant PPO alloy.
[0065] Example 1
[0066] Embodiments 1 to 5 of the present invention respectively provide a heat-resistant and shock-resistant PPO alloy, and the components and weight percentages thereof are shown in Table 1 below.
[0067] Table 1 Components and dosages in Examples 1 to 5
[0068] Example 1 Example 2 Example 3 Example 4 Example 5 PPO resin 50 60 53 57 55 PP resin 20 30 25 27 26 Titanium-containing silicone resin 10 0 7 8 8 Silicone-containing silicone resin 0 15 5 7 6 Modified filler 5 10 7 8 7 Compatibilizer 1 5 2 3 2 Toughening agent 1 5 3 5 4 Flame retardants 1 5 5 10 8 Antioxidants 0.5 2.5 1 2 2 Lubricants 0.5 2.5 1 2 1 Dispersants 1 5 1 2 1
[0069] In Examples 1 to 5, the PPO resin used is a resin material with a brand name of LXR035 purchased from Nantong Xingchen Synthetic Materials Co., Ltd., the PP resin used is a resin material with a brand name of ES-110M purchased from SK Chemical (Suzhou) Co., Ltd., the compatibilizer used is a PP-G-MAH material with a product number of 1308121823 purchased from Shanghai Koraman Reagent Co., Ltd., the toughening agent used is a chlorinated polyethylene with a brand name of CPE135A purchased from Zibo Huaxing Additive Co., Ltd., the flame retardant used is ammonium polyphosphate with a CAS number of 68333-79-9 purchased from Shandong Kunteng Chemical Co., Ltd., the antioxidant used is an antioxidant DSTDP purchased from Changzhou Xin Ce Polymer Materials Co., Ltd., the lubricant used is stearic acid erucamide 212 with a product number of Crodamide 212-1 purchased from Dongguan Dingxin Plastic Raw Materials Co., Ltd., and the dispersant used is polyvinyl alcohol 2488 purchased from Henan Youchuang Chemical Products Co., Ltd.
[0070] In Examples 1 to 5, the preparation method of the titanium-containing silicone resin used includes: mixing and dissolving 10 parts of trimethylchlorosilane, 20 parts of tetraethoxysilane and 2 parts of n-butyl titanate, by mass, in 50 parts of an aqueous solution having a volume fraction of 30% ethanol, stirring the reaction at 80° C. for 3 hours and then cooling to room temperature, extracting with toluene and separating the organic phase, and then spin-drying and recovering the toluene to obtain the titanium-containing silicone resin.
[0071] In Examples 1 to 5, the preparation method of the boron-containing silicone resin used includes: dissolving 3 mol of phenyltriethoxysilane, 3 mol of dimethyldiethoxysilane, and 2 mol of boric acid in anhydrous ethanol to obtain a dissolving solution; adjusting the pH of the dissolving solution to 1 with hydrochloric acid, stirring the hydrolysis reaction for 2 hours to obtain a hydrolyzed solution; stirring the hydrolyzed solution at 100°C for 2 hours, and then distilling it under reduced pressure to obtain a boron-containing silicone resin.
[0072] In Examples 1 to 5, the preparation method of the modified filler used comprises the following steps:
[0073] S1. Mix nano boron nitride (purchased from Haixiaohuang Nanotechnology Co., Ltd. with a product number of XH-BN-80) in anhydrous ethanol at a solid-liquid ratio of 0.07 g / mL, transfer to a sealed container, perform ultrasonic treatment, heat and boil the ethanol at pressure for 2 h, and then cool to room temperature to obtain a dispersion;
[0074] S2, add concentrated sulfuric acid dropwise into the dispersion and stir and mix rapidly, adjust to pH=2, perform ultrasonic treatment for 2h and filter, rinse the solid obtained by filtration with anhydrous ethanol and deionized water for three times, transfer the washed solid to a 50°C drying oven and dry to constant weight to obtain an activated filler;
[0075] S3, ultrasonically dispersing the activated filler into a saturated aqueous solution of melamine, filtering after ultrasonic reaction for 2 hours, rinsing the solid obtained by filtration with deionized water, transferring to a 50° C. drying oven and drying to constant weight to obtain a modified intermediate; wherein the mass mixing ratio of the activated filler to the melamine solute is 1:15;
[0076] S4. Ultrasonic dispersion of the modified intermediate into a saturated aqueous solution of dopamine hydrochloride, ultrasonic reaction for 2 hours, and then filtration. The solid obtained by filtration is rinsed with deionized water, and then transferred to a 50°C drying oven and dried to constant weight to obtain a modified filler; wherein the mass mixing ratio of the modified intermediate to dopamine hydrochloride is 8:1.
[0077] The preparation method of the heat-resistant and shock-resistant PPO alloy in Examples 1 to 5 comprises the following steps:
[0078] Y1. Premixing PPO resin, PP resin, titanium-containing silicone resin, silicon-containing silicone resin, compatibilizer, toughening agent, flame retardant, antioxidant, lubricant and dispersant to obtain a primary mixture;
[0079] Y2. The primary mixed material and the modified filler are mixed and then fed into a twin-screw extruder. After melt blending at 230° C., the screw speed is controlled to 150 rpm, and the alloy particles are obtained by extrusion, cooling, cutting and granulation.
[0080] Y3. The alloy particles are fed into an injection molding machine, melted at 250°C and injected into a molding mold preheated at 70°C, and cooled and molded to obtain a heat-resistant and impact-resistant PPO alloy.
[0081] Example 6
[0082] This embodiment 6 provides a heat-resistant and shock-resistant PPO alloy, which is different from embodiment 5 in that the preparation method of the modified filler used in embodiment 6 comprises the following steps:
[0083] S1. After mixing nano boron nitride (purchased from Shanghai Xiaohuang Nanotechnology Co., Ltd. with a product number of XH-BN-80) and a coupling agent in a mass ratio of 1:0.2, mix them in anhydrous ethanol at a solid-liquid ratio of 0.07 g / mL, transfer them to a sealed container for ultrasonic treatment, heat and boil the ethanol at pressure for 2 hours, and then cool to room temperature to obtain a dispersion; wherein the coupling agent is aniline methyl triethoxysilane (CAS: 3473-76-5, purchased from Hubei Chengfeng Chemical Co., Ltd.) and KH-540 (CAS: 13822-56-5, purchased from Hangzhou Jessica Chemical Co., Ltd.) in a mass ratio of 1:1;
[0084] S2, add concentrated sulfuric acid dropwise into the dispersion and stir and mix rapidly, adjust to pH=2, perform ultrasonic treatment for 2h and filter, rinse the solid obtained by filtration with anhydrous ethanol and deionized water for three times, transfer the washed solid to a 50°C drying oven and dry to constant weight to obtain an activated filler;
[0085] S3, ultrasonically dispersing the activated filler into a saturated aqueous solution of melamine, filtering after ultrasonic reaction for 2 hours, rinsing the solid obtained by filtration with deionized water, transferring to a 50° C. drying oven and drying to constant weight to obtain a modified intermediate; wherein the mass mixing ratio of the activated filler to the melamine solute is 1:15;
[0086] S4. Ultrasonic dispersion of the modified intermediate into a saturated aqueous solution of dopamine hydrochloride, ultrasonic reaction for 2 hours, and then filtration. The solid obtained by filtration is rinsed with deionized water, and then transferred to a 50°C drying oven and dried to constant weight to obtain a modified filler; wherein the mass mixing ratio of the modified intermediate to dopamine hydrochloride is 8:1.
[0087] Comparative Example 1
[0088] This comparative example 1 provides a heat-resistant and shock-resistant PPO alloy, which is different from Example 6 in that no modified filler is added to the PPO alloy of comparative example 1, but an equal amount of nano-boron nitride is used instead.
[0089] Comparative Example 2
[0090] This comparative example 2 provides a heat-resistant and shock-resistant PPO alloy, which is different from Example 6 in that the preparation method of the modified filler used in comparative example 2 comprises the following steps:
[0091] S1. After mixing nano boron nitride (purchased from Haixiaohuang Nanotechnology Co., Ltd. with a product number of XH-BN-80) and a coupling agent in a mass ratio of 1:0.2, mix them in anhydrous ethanol at a solid-liquid ratio of 0.07 g / mL, transfer them to a sealed container for ultrasonic treatment, heat and boil the ethanol at pressure for 2 hours, and then cool to room temperature to obtain a dispersion; wherein the coupling agent is anilinemethyltriethoxysilane (CAS: 3473-76-5, purchased from Hubei Chengfeng Chemical Co., Ltd.) and KH-540 (CAS: 13822-56-5, purchased from Hangzhou Jessica Chemical Co., Ltd.) in a mass ratio of 1:1;
[0092] S2, add concentrated sulfuric acid dropwise into the dispersion and stir and mix rapidly, adjust to pH=2, perform ultrasonic treatment for 2h and filter, rinse the solid obtained by filtration with anhydrous ethanol and deionized water for three times, transfer the washed solid to a 50°C drying oven and dry to constant weight to obtain an activated filler;
[0093] S3. Ultrasonic dispersion of the activated filler into a saturated aqueous solution of melamine, ultrasonic reaction for 2 hours, and then filtration. The solid obtained by filtration is rinsed with deionized water, and then transferred to a 50°C drying oven and dried to constant weight to obtain a modified filler; wherein the mass mixing ratio of the activated filler to the melamine solute is 1:15.
[0094] Comparative Example 3
[0095] Comparative Example 3 provides a heat-resistant and shock-resistant PPO alloy, which is different from Example 6 in that the preparation method of the modified filler used in Comparative Example 3 comprises the following steps:
[0096] S1. After mixing nano boron nitride (purchased from Haixiaohuang Nanotechnology Co., Ltd. with a product number of XH-BN-80) and a coupling agent in a mass ratio of 1:0.2, mix them in anhydrous ethanol at a solid-liquid ratio of 0.07 g / mL, transfer them to a sealed container for ultrasonic treatment, heat and boil the ethanol at pressure for 2 hours, and then cool to room temperature to obtain a dispersion; wherein the coupling agent is anilinemethyltriethoxysilane (CAS: 3473-76-5, purchased from Hubei Chengfeng Chemical Co., Ltd.) and KH-540 (CAS: 13822-56-5, purchased from Hangzhou Jessica Chemical Co., Ltd.) in a mass ratio of 1:1;
[0097] S2, add concentrated sulfuric acid dropwise into the dispersion and stir and mix rapidly, adjust to pH=2, perform ultrasonic treatment for 2h and filter, rinse the solid obtained by filtration with anhydrous ethanol and deionized water for three times, transfer the washed solid to a 50°C drying oven and dry to constant weight to obtain an activated filler;
[0098] S3. Ultrasonic dispersion of the activated filler into a saturated aqueous solution of dopamine hydrochloride, ultrasonic reaction for 2 hours, and then filtration. The solid obtained by filtration is rinsed with deionized water, and then transferred to a 50°C drying oven and dried to constant weight to obtain a modified filler; wherein the mass mixing ratio of the activated filler to dopamine hydrochloride is 8:1.
[0099] Performance Testing
[0100] The PPO alloys prepared in Examples 1 to 6 and Comparative Examples 1 to 3 were tested for the following items, and the test results are shown in Table 2 below:
[0101] Tensile strength, tested based on ASTM D638 standard;
[0102] Flexural strength, tested based on ASTM D790 standard;
[0103] Notched impact strength is tested based on ASTM D256 standard.
[0104] The PPO alloys prepared in Examples 1 to 6 and Comparative Examples 1 to 6 were aged in an oxygen atmosphere at 90°C for 12 hours and then cooled to room temperature. The above items were tested and the tensile strength retention rate, bending strength retention rate and impact strength retention rate were calculated. The results are shown in Table 2 below.
[0105] Table 2 Performance test data
[0106]
[0107]
[0108] As can be seen from Table 2, the tensile strength data of Examples 1 to 6 show that the introduction of titanium-containing and boron-containing silicone resins and modified fillers significantly improves the tensile strength of the PPO / PP alloy. By comparison, it is found that the initial tensile strength of Example 2 is the highest (64.5MPa), indicating that the boron-containing silicone resin has a significant effect in improving the initial strength, and the retention rate of Example 6 is the highest (93.78%), indicating that the dispersibility and surface modification effects of the modified filler are obvious, and can effectively improve the heat resistance and stability of the material.
[0109] In contrast, the tensile strengths of Comparative Examples 1 to 3 are significantly lower, especially Comparative Example 1, whose initial strength is only 43.5 MPa, and the retention rate after aging is also the lowest (78.62%). This shows that the dispersibility of unmodified nano-boron nitride is poor, resulting in poor overall performance. Although Comparative Examples 2 and 3 have improved, they are still significantly lower than the embodiment.
[0110] The bending strength test shows that the bending strength of Examples 2 to 6 is relatively high, and the bending strength retention rate after aging is relatively high, especially Example 6, which has the highest bending strength retention rate (94.24%), indicating that the dispersibility and surface modification of the modified filler have a significant effect on the bending strength. The bending strength of the comparative example is significantly lower than that of the examples, especially Comparative Example 1, whose retention rate after aging is only 74.65%, indicating that the unmodified nano boron nitride has a significant effect on the bending performance. The retention rates of Comparative Examples 2 and 3 are slightly higher than those of Comparative Example 1, but are still much lower than those of the examples, indicating that the unmodified modified filler has a poor effect.
[0111] The notched impact strength test results show that the impact resistance of Examples 2 to 6 is good, especially Example 6, which has the highest retention rate (94.80%), which verifies the significant effect of the dispersibility and surface modification of the modified filler on improving the impact resistance. The notched impact strength of the comparative example is significantly lower than that of the example, especially Comparative Example 1, whose retention rate is only 72.65%, indicating that the unmodified nano boron nitride has a poor effect in terms of impact resistance. Although Comparative Examples 2 and 3 have been improved, they are still significantly lower than the examples, indicating that the unmodified modified filler has limited improvement in impact resistance.
[0112] Although the embodiments of the present invention are described in detail above, it is obvious to those skilled in the art that various modifications and variations can be made to these embodiments. However, it should be understood that such modifications and variations are within the scope and spirit of the present invention as described in the claims. Moreover, the present invention described herein may have other embodiments and may be implemented or realized in a variety of ways.
Claims
1. A heat-resistant and shock-resistant PPO alloy, characterized in that: The invention comprises the following components in parts by weight: 50-60 parts of PPO resin, 20-30 parts of PP resin, 10-15 parts of silicone resin, 5-10 parts of modified filler and 5-25 parts of functional additive. The preparation method of the modified filler comprises: ultrasonically dispersing nano boron nitride in ethanol to obtain a dispersion; acidifying the pH value of the dispersion to 2-3, ultrasonically treating for 1-2 hours, separating, washing and drying to obtain an activated filler; ultrasonically dispersing the activated filler in a melamine solution, and then separating to obtain a modified intermediate; ultrasonically dispersing the modified intermediate in a dopamine hydrochloride solution, reacting for 10-15 hours at a pH value of 8-9, and then separating and drying to obtain a modified filler.
2. The PPO alloy according to claim 1, characterized in that When the modified intermediate is ultrasonically dispersed in the dopamine hydrochloride solution, the mass mixing ratio of the modified intermediate to the dopamine hydrochloride solute in the dopamine hydrochloride solution is (5-10):
1.
3. The PPO alloy according to claim 1, characterized in that When the nano boron nitride is ultrasonically dispersed in ethanol to obtain the dispersion liquid, the method comprises: mixing the nano boron nitride with a coupling agent, putting the mixture into the ethanol, and then ultrasonically dispersing the mixture to obtain the dispersion liquid.
4. The PPO alloy according to claim 3, characterized in that The coupling agent includes at least one of a silane coupling agent and a titanate coupling agent; and / or, the mass mixing ratio of the nano boron nitride to the coupling agent is 1:(0.2-0.3).
5. The PPO alloy according to claim 1, characterized in that The average particle size of the nano boron nitride is 20-100 nm.
6. The PPO alloy according to any one of claims 1 to 5, characterized in that: The functional additives include compatibilizers, toughening agents, flame retardants, antioxidants, lubricants and dispersants.
7. The PPO alloy according to claim 6, characterized in that: The compatibilizer includes at least one of PP-G-MAH, PE-G-MAH, POE-G-MAH, EPDM-G-MAH, and SEBS-G-MAH; And / or, the toughening agent includes at least one of chlorinated polyethylene, ethylene-vinyl acetate copolymer, and nitrile resin; And / or, the flame retardant includes at least one of polyphosphoamine, p-hydroxybenzoic acid, and triisobutylphenyl phosphate; And / or, the antioxidant includes at least one of dialkyl pentaerythritol diphosphite, dioctadecyl pentaerythritol diphosphite, bis(2,4-di-tert-butylphenol)pentaerythritol diphosphite, and tetrakis(2,4-di-tert-butylphenyl-4,4'-biphenyl)bisphosphate; and / or, the lubricant comprises at least one of erucamide, oleamide, stearamide, zinc stearate, magnesium stearate and calcium stearate; And / or, the dispersant includes at least one of polyvinyl alcohol, casein and cellulose.
8. The PPO alloy according to claim 6, characterized in that The composition comprises the following components in parts by weight: 53-57 parts of PPO resin, 25-27 parts of PP resin, 12-15 parts of silicone resin, 7-8 parts of modified filler, 2-3 parts of compatibilizer, 3-5 parts of toughening agent, 5-10 parts of flame retardant, 1-2 parts of antioxidant, 1-2 parts of lubricant and 1-2 parts of dispersant.
9. The PPO alloy according to claim 1, characterized in that: The organic silicone resin includes a titanium-containing organic silicone resin and a boron-containing organic silicone resin, and the mass mixing ratio of the titanium-containing organic silicone resin to the silicon-containing organic silicone resin is (6-8):(4-7).
10. A process for preparing the PPO alloy according to any one of claims 1 to 9, characterized in that: The following steps are involved: The PPO resin, PP resin, silicone resin and functional additives are pre-mixed to obtain a primary mixture; the primary mixture is mixed with a modified filler, melt-blended at 200-240° C., and then extruded and pelletized to obtain alloy particles; the alloy particles are injection-molded at 200-250° C. to obtain a heat-resistant and impact-resistant PPO alloy.
Citation Information
Patent Citations
High-strength polyphenyl ether / polypropylene blended alloy material and preparation method thereof
CN104277403A
Polyphenylene oxide (PPO) alloy resistant to chemicals, steaming and boiling and preparation method thereof
CN108997734A